Cuidado em território de exclusão social: covid-19 expõe marcas coloniais - Camilo, Claudia; Kahhale, Edna; Ferreira, Maria Luísa; Schveitzer, Mariana (Saúde e Sociedade, 2021)
A intersecção de gênero, raça e classe marca os territórios de exclusão social, especialmente em um país que carrega cicatrizes da colonialidade patriarcal e capitalista em suas estruturas, como é o caso do Brasil. O objetivo deste trabalho é compreender o cuidado em um desses territórios: a cidade de Cubatão/SP. A investigação, feita entre 2017 e 2020, incluiu a pandemia da covid-19, que sobrecarregou o cuidado no território. O método foi a pesquisa qualitativa, com oficinas, observação participante e entrevistas de profundidade. O cuidado era majoritariamente oferecido por mulheres, líderes comunitárias e profissionais da atenção primária do Sistema Único de Saúde. Para analisar os dados, utilizou-se a hermenêutica de profundidade. O referencial teórico foi a costura das teorias feministas da ética do cuidado, ecofeministas e interseccionais. A pesquisa revelou diversos desafios e potencialidades, como o cuidado ético-político, eixo da busca por justiça socioambiental. , Abstract The intersection of gender, race and class marks the territories of social exclusion, especially in a country that carries scars of a patriarchal and capitalist colonialism in its structures, as is the case in Brazil. The objective was to understand care in this territory of exclusion in Cubatão, São Paulo, Brazil. The research, conducted between 2017 and 2020, included the pandemic of COVID-19, which overloaded care in this territory. The method was qualitative research, with workshops, participant observation and in-depth interviews. The care delivered by community leaders and primary health care professionals from the Brazilian National Health System was mostly performed by women. For data analysis, depth hermeneutics was used. The theoretical reference was the perspective of feminists: ecofeminist, intersectional and Care Ethics. The study showed several challenges and the ethical-political care as an axis in the search for social and environmental justice.
http://www.scielo.br/scielo.php?script=sci_arttext&pid=S0104-12902021000200202&tlng=pt
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; brésil; care; covid-19; intersectionnalité; pandémie; patriarcat; projet charge mentale; périodes historiques; racisme; régions géographiques; système colonial; systèmes d'oppressions; thématiques; travail; écoféminisme

Hidden in plain sight: Uncovering the emotional labor of Black women students at historically White colleges and universities. - Kelly, Bridget T.; Gardner, Paige J.; Stone, Joakina; Hixson, Ashley; Dissassa, Di-Tu (Journal of Diversity in Higher Education, 2021)
We utilized the emotional labor triangle to understand how 16 Black women students who attended Historically white colleges and universities (HWCUs) navigated gendered-racialized oppressive environments that mattered to their academic success. This study contributes to a gap in the literature, as much of the research focused on students of color without disaggregating for gender or other social identities. In addition, the literature is scant on experiences of Black women students use of emotional labor. Emotional labor has largely been studied from a management perspective. Through qualitative semi-structured interviews, we examined the emotional labor Black women expended while pursuing their undergraduate degree. We employed a qualitative, intersectional, methodological approach to foreground historically marginalized voices and situated the study in the hypervisibility Black women participants described feeling as space invaders on their historically White undergraduate campus and at the same time the invisibleness of their voice and masking of their feelings as they encountered gendered racism. Further, we emphasized the emotional toll and stress that may occur for Black women when they do not utilize engaged coping mechanisms while expending their emotional labor. The study holds implications for educators to address emotional labor inequities within HWCUs. (PsycInfo Database Record (c) 2021 APA, all rights reserved) © 2019 National Association of Diversity Officers in Higher Education
Number: 2
Keywords: amériques; approches et analyses; care; colère; femmes universitaires noires*; intersectionnalité; projet charge mentale; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail; travail émotionnel; violences; états-unis

Sexual citizenship through resistance: a movement that centers disabled women’s voices - MacKeigan, Tanya (Disability & Society, 2021)
This research examines the discourses that shape disabled women’s sexual subjectivity. I wanted to see how disabled women’s understanding of themselves as sexual is socially influenced. I held a focus group and individually interviewed five self-identified physically disabled women about their sexual lives. They shared detailed stories of personal experiences and societal influences. The main social influences that were present in the women’s stories were ableism, sexism, and resistance; the focus of this article is resistance. Resistance discourses challenge mainstream notions of disability and sexuality and combat the oppression that ableism and sexism can create. It is important work to highlight these resistance narratives; they are often overlooked in society. Diverse social understandings of disability and sexuality are needed, and it is important that they come from disabled people. This research seeks to make space for disabled perspectives in the interest of sexual inclusivity and sexual citizenship for disabled women.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; EDI; accessibilité; amériques; approches et analyses; canada; capacitisme; care; colombie-britannique; corps; cours; discipline; droit des personnes en situation de handicap; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex1911; sex1920; sexisme; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Féminismes et pop culture - Padjemi, Jennifer (Éditions Stock, 2021)
"Dans un essai passionné et engagé, Jennifer Padjemi explore l'alliance, pour le meilleur et pour le pire, des féminismes et de la pop culture. A partir des mouvements féministes modernes, elle décortique le rapport que nous entretenons avec les objets culturels les plus populaires. En utilisant la pop culture comme un miroir de notre société mondialisée, l'auteure interroge les liens d'interdépendance entre consommation de masse et idéologie progressiste, et jette un regard joyeux et lucide sur nos divertissements, sans concession au patriarcat."–Quatrième de couverture.
Section: 283 pages ; 18 cm.
Keywords: afro-féminisme; approches et analyses; care; communication; corps; cours; discipline; féminisme afropéen; féminisme pop; féminismes noirs; intersectionnalité; journalisme; premier cycle; sex2283; sexualité; thématiques; écriture des femmes*; études culturelles

Gendered care work and environmental injustice: A feminist analysis of educator's emotional labor in disaster recovery - Shtob, Daniel A.; Petrucci, Larissa (Environmental Justice, 2021)
Although environmental justice researchers have long been interested in the connections between disaster recovery, gender, and home- and community-based care, the consequences of the post-disaster performance of emotional labor by workers in care occupations have largely gone unnoticed. To address this gap in the environmental injustice literature, in this exploratory article we employ a feminist analysis of firsthand accounts of elementary educators' professional and personal experiences caring for their students in the Florida Keys after Hurricane Irma. We find that caring labor was increasingly necessary in the post-disaster context, both inside and outside the classroom. Teachers and other care professionals in feminized occupations may, therefore, perform an emotional double duty, supporting their students' emotional needs while also contending—as working- and middle-class individuals—with the personal consequences of disaster. We suggest that these educators may bear an unrecognized and undercompensated disproportionate burden at the intersection of class and occupational status. Because of this, we introduce an underexplored component to the racialized disaster patriarchy and intersectional disaster research: feminized occupational status. Inspired by environmental justice research legacies developed in the wake of earlier Gulf Coast disasters, we draw attention to the contributions of these absolutely essential recovery workers and how they may experience environmental injustice even as they contribute to others' recovery. Our goals are to promote recognition and fair distribution of burdens, encourage research into the contours of environmental justice and care work, and support the development of more just planning, training, and compensation regimes.
Keywords: amériques; approches et analyses; care; discipline; floride; intersectionnalité; patriarcat; projet charge mentale; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail; émotions

The Routledge handbook of disability and sexuality - Shuttleworth, Russell; Mona, Linda (Routledge, 2021)
This handbook provides a much-needed holistic overview of disability and sexuality research andscholarship. With authors from a wide range of disciplines and representing a diversity of nationalities, it provides a multi-perspectival view that fully captures the diversity of issues and outlooks. Organised into six parts, the contributors explore long-standing issues such as the psychological, interpersonal, social, political and cultural barriers to sexual access that idsabled people face and their struggle for sexual rights and participation. The volume also engages issues that have been on the periphery of the discourse, such as sexual accomodations and support aimed at facilitating disabled people's sexual well-being; the socio-sexual tensions confronting disabled people with intersecting stigmatised identities such as LGBTBI or asexual; and the sexual concerns of disabled people in the Global South. It interrogates disability and sexuality from diverse perspectives, from more traditional psychological and sociological models, to various subversive and post-theoretical perspectives and queer theory. This handbook examines the cutting-edge, and sometimes ethically contentious, concerns that have been repressed in the field. With current, international and comprehensive content, this book is essential reading for students, academics and researchers in the areas of disability, gender and sexuality, as well as applied disciplines such as healthcare pratictionners, counsellors, psychology trainees and social workers.
Le texte Santinele Martino, A. et Fudge Schormans, A. (2021). Theoretical developments: Queer theory meets crip theory a été donné en lecture au cours SEX1920
Keywords: EDI; LGBTQIA2+; accessibilité; approches et analyses; capacitisme; care; corps; cours; discipline; histoire et politique; identités LGBTQIA2+; intersectionnalité; outils; ouvrages de références; premier cycle; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1911; sex1920; sexologie; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Informal caregiving and strains: Exploring the impacts of gender, race, and income - Willert, Bria; Minnotte, Krysta Lynn (Applied Research in Quality of Life, 2021)
Informal caregivers are those who provide care for others without compensation. In the US, 85 % of elderly individuals receive care from an informal caregiver, and this number is expected to increase. Caregivers often experience different types of strain, stemming from physical, emotional, and financial demands. Guided by intersectionality theory, this study explores the relationships between informal caregiving strains and gender, race, and income, along with various control variables, including age, marital status, education, number of hours spent providing care, and employment status. Data from the 2015 Caregiving in the US survey (N = 1248) were used. Findings indicated male informal caregivers reported more financial strain compared to females. White women reported more emotional strain than women of color, and those with higher incomes reported less financial strain. Gender, race, and income were not significantly related to physical strain among informal caregivers. Implications, limitations, and suggestions for future research are discussed. © 2019, The International Society for Quality-of-Life Studies (ISQOLS) and Springer Nature B.V.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; care; détresse psychologique; intersectionnalité; proche aidance; projet charge mentale; périodes historiques; régions géographiques; soins aux; stress financier; thématiques; états-unis